A self-adjuvant multiantigenic nanovaccines simultaneously activate the antiviral and antitumor immunity for the treatment of cancers - Zhongjie Wang; Hanlin Chen; Ruiqi Ming; Weiwei Wang; Shujun Liu; Yuantian Jing; Zewei Yan; Guihong Lu; Li-Li Huang (Journal of Nanobiotechnology)
Abstract Background Tumor cell-derived extracellular vesicles (tEVs) have garnered significant attention as promising antigen delivery vehicles for the development of cancer vaccines. However, their practical applications are hindered by weak immunogenicity and inadequate lymph node targeting. In this study, we engineered tEVs into “self-adjuvant” multiantigenic nanovaccines that simultaneously accumulate in tumors and lymph nodes (LNs), effectively triggering innate and adaptive immunity capable of recognizing both tumor cells and virus antigen-modified tumor cells to inhibit tumor progression. Results 4T1 tumor cells were infected with vesicular stomatitis virus (VSV), leading to the expression of VSVG and calreticulin (CRT) on their surface. Using these infected cells, we prepared extracellular vesicles (vEVs) carrying both VSVG and CRT. When injected subcutaneously, vEVs targeted tumors effectively due to the homologous targeting capability of tumor cell membranes. In which, VSVG induced fusion between vEVs and tumor cells, creating viral antigen-decorated tumor cells, which enhanced the recognition and phagocytosis of tumor cells by macrophages. Additionally, the surface CRT of vEVs activated the “eat-me” signaling, thus improving their recognition and uptake by dendritic cells (DCs). This led to DC maturation and the activation of antiviral and antitumor T cells, synergistically inhibiting tumor growth. Conclusions This research introduces a straightforward yet efficacious methodology for the production of cancer vaccines to fight cancer through the stimulation of both the antiviral and antitumor immune responses within the body. Graphical abstract